Deep Genomic Sequencing of Bladder Urothelial Carcinoma in Southern Chinese Patients: A Single-Center Study - Li, Dong-Yang; Yang, Fei; Liao, Wei-Qiang; Zhou, Xiang-Fu; Li, Wen-Biao; Cai, Jia-Rong; Liu, Bo-Long; Luo, Yun; Zhan, Hai-Lun (Frontiers in Oncology, 2021)
Objective: Bladder urothelial carcinoma (BUC) is a common urological malignancy with molecular heterogeneity. However, the genetic feature of Chinese BUC patients is still not well-identified. Methods: We performed deep sequencing by a large panel (450 genes) on 22 BUC samples and using matched normal bladder tissue as control. Genomic alterations (GAs), pathways and Tumor Mutation Burden (TMB) were investigated. Results: The frequencies of GAs (TERT, 54.5%; CREBBP, 27.3%; GATA3, 22.7%; BRAF, 18.2%; TEK, 18.2% and GLI1, 18.2%) were significantly higher in Chinese than Western BUC patients. Other GAs’ frequencies were in accordance with previous study (TP53, 50.0%; KDM6A, 31.8%; KMT2D, 22.7%; etc.). Besides, we detected gene amplification in ERBB2, FRS2, FAS, etc. The gene fusion/rearrangement took place in the chromosome 11, 12, 14, 17, 19, 22, and Y. Other than cell cycle and PI3K-AKT-mTOR, mutated genes were more associated with the transcription factor, chromatin modification signaling pathways. Interestingly, the TMB value was significantly higher in the BUC patients at stage T1-T2 than T3-T4 (P=0.025). Conclusion: Deep genomic sequencing of BUC can provide new clues on the unique GAs of Chinese patients and assist in therapeutic decision.